Expectation Formation and Financial Ratio Adjustment: A Reply - Lee, Cheng F. (Institutional Knowledge at Singapore Management University, 1993)
In a reply, Cheng and Wu note that Tung and Crowe (1993) in their comment on Lee and Wu (1988) suggest an alternative method based on the distributed lag form of adaptive expectations for estimating the parameters of the partial adjustment and adaptive expectations model. Tung and Crowe claim the method has resolved the ambiguity problem of parameter estimation. The reply indicates the pitfalls of the proposed statistical procedure and suggests a possible extension.